Ways to optimize steppe under of oil and gas production - К. V. Myachina; E. V. Krasnov (Юг России: экология, развитие, 2021)
Aim. To substantiate ways of geo‐ecological optimization of an oil and gas field landscape (through the example of the Volga‐Ural steppe region).Materials and Methods. The development of directions for geoecological optimization of landscape is based on the authors’ previously developed ideas about the transformation processes of landscape, the formation and stages of the oil and gas natural‐technogenic geosystem development, and the hierarchy and multi‐scale of technogenic changes of landscape.Results. Optimization solutions were developed for the successive stages of planning of oil and gas extraction, operation of an oil and gas natural‐technogenic geosystem field and the end of development and disposal of oil and gas facilities. The main direction of landscape optimization is highlighted and its tasks and principles formulated.Conclusion. Reducing technogenic impact on steppe landscape, its control and regulation is not only a problem of scientific research, but also one of the state of public consciousness and the setting of priorities by management bodies. Methods of reducing the impact and restoringsteppe landscapes can only be effective as a result of implementing a targeted policy of greening education and a corresponding change in public consciousness.